Relationship Between Self Control And Bullying Behavior Trends in Students of SMP N 15 Padang - Andre Setiawan; Alizamar Alizamar (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of many teenagers who tend to behave in bullying, such as chiding, hitting, spitting, throwing, calling names with labels, threatening, and frightening. Bullying behavior is a negative behavior that is thought to be one of the contributing factors is low self control. This study aims to reveal the relationship of self-control with the tendency of bullying behavior of students. This research is a descriptive and correlational type of research with quantitative methods. The sample in this study were 256 students consisting of classes VII, VIII and IX. The data collection instrument was a self-control questionnaire with a tendency for bullying behavior in students using the Likert scale. The data is processed using Pearson product moment formula with the Statical Product and Service Solution (SPSS) program version 20.0. The results of this study reveal that there is a relationship of self-control with the tendency of bullying behavior of students, high or low self-control will affect the tendency of bullying behavior. Based on the findings of this study, it is expected that the BK counselor or counselor can provide assistance and services in the form of guidance and counseling services.